Nutrition management for preterm infants to avoid growth faltering in later days - Dilantika, Charisma; Wasito, Erika; Fathiya, Dina Nurul (Journal of Indonesian Specialized Nutrition, 2024)
Premature babies have a high risk of experiencing growth retardation due to the inability of their organs to function optimally, including in absorbing nutrients. The early period of life is a critical period that requires proper nutritional management to support optimal growth and development. This study aims to provide recommendations for optimal steps for nutritional management in premature babies so that growth retardation can be avoided. The results showed that the basic principles of preterm infant nutrition management involve strategic steps to optimally meet nutritional needs. The first step is exclusive breastfeeding, which is the best source of nutrition. If breast milk is insufficient, specialized formula milk is an important alternative. Other nutritional management includes enteral and parenteral nutrition, tailored to the infant's condition. Monitoring growth and development, food tolerance and body composition are key elements to ensure the success of the intervention. Collaboration between the healthcare team, including doctors, nurses, nutritionists and parents, is essential in this process. With a careful approach and monitoring, nutritional management can address the challenges of premature infants, providing a better chance of achieving optimal health and development in the future.